EVALUASI SISTEM INFORMASI PEMBAYARAN MENGUNAKAN FRAMEWORK COBIT 4.1 - Faizal Gunawan; Sri Siswanti; Andriani Kusumaningrum (STMIK Sinar Nusantara, 2018)
University of Tunas Pembangunan Surakarta is one of the universities in Surakarta. University of Tunas Pembangunan utilizes IT in the utilization and management of its organizational processes, especially in payments using financial information systems. The focus of the problem by the payment service provider is the information system that has not been integrated with the bank, data input is still using proof of payment from the bank and then in the manual input by staff BAUK. Problems that occur are the strokes in inputting data, the number of queues during student activation, and the length of the flow during KRS activation. This research uses COBIT 4.1 Framework with DS1 and DS11 domain process. The degree of maturity to evaluate payment service providers for Financial Information Systems is at Level 3 (Process Defined). This is in accordance with the current state of financial information management. The expected maturity level in BAUK is 5 (Optimized) then from what it is and there should be a gap emerging then given recommendations to make improvements to the desired level of maturity achieved.